الاتجاهات السوسيواقتصادية للشباب الجامعي نحو العمل في القطاع العام دراسة ميدانية على عينة من طلبة سنة ثانية ماستر بقسم علم الاجتماع و الديمغرافيا كلية العلوم الاجتماعية جامعة الأغواط - بلبالي عائشة; هراو ريم; سويسي أحمد (My University, 2023)
This study aimed to identify the socioeconomic trends of university youth to wards working in the public sector ,Through a field study on students who are about to graduate in the second year of a master's degree in sociology in all its disciplines, we attempted to identify the most significant factor that attracts this group to work in the public sector. By understanding the impact of material and moral incentives in this, as well as the impact of the management pattern for the study, we were able to identify the socioeconomic trends of university youth toward working in the public sector. It was discovered that the majority of college students prefer to work in government because of both material and ethical motivations, such as social security, retirement benefits, and organizational culture. Key words : Trends, youth, university youth, the public sector